2012
DOI: 10.1002/chp.21150
|View full text |Cite
|
Sign up to set email alerts
|

Improving Quality in Systems of Care: Solving Complicated Challenges with Simulation-Based Continuing Professional Development

Abstract: The delivery of quality health care depends on the successful interactions of practitioners, teams, and systems of care comprising culture. Designing educational programs to improve these interactions is a major goal of continuing professional development, and one approach for educational planners to effect desired changes is simulation-based education. Because simulation-based education affords an opportunity for educators to train health care professionals in environments that resemble clinical practice, thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…IPE is a possible solution to some of these issues as interprofessional working has helped decrease medical errors and helped improve patient satisfaction, patient care and knowledge and skills of professionals [4]. Knowledge of different working practices and awareness of different professional accountabilities, roles and competencies are pivotal in driving improved healthcare [5,6]. Working together for patients requires teamwork and an appreciation of not only the types of services provided but of the providers themselves [7,8], which makes IPE highly relevant.…”
Section: Introductionmentioning
confidence: 99%
“…IPE is a possible solution to some of these issues as interprofessional working has helped decrease medical errors and helped improve patient satisfaction, patient care and knowledge and skills of professionals [4]. Knowledge of different working practices and awareness of different professional accountabilities, roles and competencies are pivotal in driving improved healthcare [5,6]. Working together for patients requires teamwork and an appreciation of not only the types of services provided but of the providers themselves [7,8], which makes IPE highly relevant.…”
Section: Introductionmentioning
confidence: 99%
“…Recently published guidance for developing simulations can be found in Chiniara, 24 Petrusa, 25 Issenberg, 26,27 and several articles that recently appeared in a JCEHP theme issue addressing human factors and simulation. [28][29][30][31][32][33][34] Simulation can also contribute to CEHP by supporting continuous learning in a system of care. 35 In such a system, learning would be ongoing and augmented with "just-intime" access to information in the clinical workflow.…”
Section: Simulationmentioning
confidence: 98%
“…Ultimately SBE is a tool that offers many advantages over traditional education delivery such as lectures, courses, and workshops [2]. However, it cannot work in isolation and must be integrated into curricula to achieve the competencies or learning objectives set out by governing bodies across the various disciplines.…”
Section: Challenges In Competency-based Simulation Educationmentioning
confidence: 99%
“…In response, accrediting bodies, healthcare organizations, and medical educators across all disciplines have embraced SBE as one solution to improving what many believe was a root cause, namely poor communication and team functioning [2]. A burgeoning literature in SBE has demonstrated that simulation can improve knowledge, skills, and behaviors as well as result in some improvement in patient outcomes [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%